Un modelo de neto patrimonial con inversiones productivas coordinadas - Mocholí Arce, Manuel; Navarro Miquel, Valentín (Rect@, 2013)
The investment and financing decisions in companies are related because both generate cash flows, often uncertain. The Investment decisions main function is the efficient allocation of financial resources to projects that will contribute to the future profitability of the company, and they determine the volume and types of assets in which the company must invest. Financing decisions’ function is to determine the proportion of own resources and external resources, which form the financial structure of the company, i.e. its debt and its cost of capital. Both functions are interrelated, since each is conditioned by the other. In this paper we propose a model of Net Asset Maximization (NAM) in the medium and long term for an industrial company. The proposed model considers that there is uncertainty about the future demand for items produced by the firm, which affects the financial decisions that company should take (investment-financing, dividends, liquidity.). The uncertainty related to the demand is analyzed by generating multiple scenarios and then a coordinated model is proposed ensuring the robustness of the solution obtained.